Designing a secure positioning system using blockchain technology. (17th April 2020) - Singh, Rajrupa; Selvakumar, R.
Achieving a secure positioning system is one of the most prominent issues in the field of wireless security. The central task of this paper is introducing a system that is provably secure for sharing the most sensitive data among the users in a peer-to-peer network. In such systems, the geographical position of the users or the nodes in the network plays a vital role in maintaining the security of the entire network especially for defence purpose. Apart from the existing bounded storage models, the system gives a positive result for 'secure positioning problem'. The designing of the proposed system is based on the network, where the public ledger is maintained by all the nodes independently without any central authority. This zero knowledge protocol proposed in this paper makes the search space size to grow exponentially, which is a major challenge for the intruder to prove their position.